Reversible computation : 11th International Conference, RC 2019, Lausanne, Switzerland, June 24u201325, 2019, proceedings /: 11th International Conference, RC 2019, Lausanne, Switzerland, June 24u201325, 2019, proceedings. (2019) - Unknown
No abstract available